Subthreshold laser treatment for reticular pseudodrusen secondary to age-related macular degeneration - Giuseppe Querques (Nature Portfolio, 2021)
Abstract There is a lack of treatment aimed at the regression of reticular pseudodrusen (RPD) secondary to age-related macular degeneration (AMD). The aim of this prospective, pilot study is to evaluate the safety and short-term efficacy of subthreshold laser treatment (SLT) in patients affected by RPD secondary to dry AMD (dAMD). Twenty eyes of 20 patients (mean age 78.4 ± 6.8 years) with RPD secondary to dAMD were prospectively enrolled. All patients were treated in an extrafoveal area of 1.27 mm2 using end-point management yellow subthreshold laser and followed for 3 months. Best-corrected visual acuity was 0.140 ± 0.09 LogMAR at the baseline and no changes were observed during the follow-up (p = 0.232). No significant worsening was disclosed before and after the treatment analyzing the macular sensitivity of the treated area (p = 0.152). No topical and/or systemic side effects were disclosed during the 3-month follow-up. The distribution among the RPD stages changed after the treatment (p < 0.001). In detail, in the treated area, we observed a significant increase in the number of Stage 1 RPD during the follow-up (p = 0.002), associated with a significant decrease of Stage 3 RPD (p = 0.020). Outer nuclear layer (ONL) thickness analysis showed a significant increase after the treatment associated with RPD regression (p = 0.001). End-point management SLT appears a safe treatment for RPD secondary to dAMD, showing short-term safety outcomes. Our results suggest that SLT could be effective in inducing a RPD regression in terms of RPD stage and ONL thickening.